An analysis of Indonesia's Banking Subsector reveals how Earnings Per Share, Return on Assets, Net Interest Margin, and Non-Performing Loans Affect Stock Price - Wicaksono, Heri Agung; Ernawati, Nani (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study aims to assess the impact of earnings per share (EPS), return on assets (ROA), net interest margin (NIM), and non-performing loans (NPL) on the stock price of the banking Subsector in Indonesia from 2017 to 2023. The primary focus of this research is the fluctuation in stock prices, which is influenced by various financial factors related to the companies. The methodology employed is quantitative, using panel data analysis using Eviews 13 software. The findings reveal that EPS and ROA have a significant impact on stock value, while NIM and NPL do not show meaningful effects. The study ultimately indicates that indicators such as EPS and ROA have a stronger influence on bank stock prices. Therefore, banking companies should emphasize improving these indicators to attract investor interest in purchasing stocks from the banking sector. Keywords: EPS; ROA; NIM; NPL; Stock Price